Analisis Peningkatan Suara Partai Demokrat di Sumatera Utara - HUSNUL ISA HARAHAP (Politeia: Jurnal Ilmu Politik, 2010)
The General Elections in 2009 in Indonesia showed a new phenomenon that is the end of the dominance of the old parties of the nationalist-based (Golkar and PDIP). The dominance of the old parties has been replaced by a new nationalist party (Partai Demokrat). This study aimed to look at the factors causing the increase in Partai Demokrat votes. This study found there were five factors causing the increase Partai Demokrat vote. The first factor is the persona of Susilo Bambang Yudhoyono. The second factor is the establishment candidate strategy. The third fac-tor is the success of managing internal conflicts. The fourth factor is the persona of the candi-date. The fifth factor is the performance of the Partai Demokrat. In generally, it’s true persona factor Susilo Bambang Yudhoyono has become a powerful magnet in attracting sympathy con-stituen to vote Partai Demokrat, but in that case in Sumatera Utara, local persona factors also become important element of voice improvement Partai Demokrat.Keywords: Political image, Political behavior, Local elite, Political marketing.